The presumption of innocence in the adversarial system - Felices Mendoza, María Esther (2021)
This article develops one of the most important principles of the accusatory criminal system, the presumption of innocence, which is also a right and guarantee that has been recognized in international human rights treaties, and which is part of the fundamental rights recognized in the Political Constitution of the State, which sustain the democratic rule of law, so that today it can be said that there is a constitutionalized criminal process that requires the observance of due process.